Effect of microwave heating on ph and termite resistance of Pinus roxburghii wood - Kumar Poonia, Pawan; Tripathi, Sadhna (Maderas. Ciencia y Tecnología, 2018)
This study investigated the effect of microwave treatment on wood pH and termite resistance. Pinus roxburghii heartwood was exposed to four different microwave intensities at 2450 MHz frequency for 5 minutes. Preservative impregnation, pH variation and termite resistance of microwave-treated and control specimens were studied. Wood pH decreased from 4.6 (C1) to 3.9 (T4) and preservative uptake increased (i.e., 10.41 to 21.61 kgm-3) with increasing microwave treatment intensities. However, microwave treatment had little effect on termite resistance.